Religious Authority in the New Media Era: Sabilul Huda Islamic Boarding School Da’wah on Social Media - Kuswana, Dadang; Pauzian, Muhamad Hilmi (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
This research aims to discuss religious authority in the new media era, with the object of study being the Da'wah model of the Sabilul Huda Tasikmalaya Islamic boarding school. This paper uses ethnographic and netnographic methods. Ethnography was carried out by interviews and following book studies at the Sabilul Huda Islamic boarding school. Meanwhile, netnography conducts data searches on online participants. The results and discussion of this research include the relationship between religion and social media, the Sabilul Huda Islamic Boarding School's da'wah strategy on social media, and the authority of Islamic boarding schools and kiayi on social media. This research concludes that the interaction between religion and the internet causes positive and negative impacts. Another important finding is that about religious authority, the internet and religion follow the logic of discontinuity, namely viewing the internet as destroying traditional religious authority. Moreover, at the same time, the internet and religion can also follow the logic of continuity and complementarity. The Internet extends, complements, and strengthens traditional religious authority. Then, the strategy carried out by the Sabilul Huda Islamic boarding school in preaching and spreading its traditional religious sources on social media is carried out by live streaming the study of the Yellow Book on social media accounts, namely Sabilulhudamedia. Then, the authority of the traditional and charismaticÂ KiaiÂ is preserved by carrying out his preaching via social media. This research implies that this new da'wah model that utilizes online media keeps the influence of traditional religious authorities and Islamic boarding schoolÂ Kiai.